Clinico-haematological studies on experimentally induced chronic selenosis in buffalo calves * - SINGH, RATTANDEEP; RANDHAWA, S S; DHILLON, K S; DHILLON, S K (The Indian Journal of Animal Sciences, 2014)
Clinico-haematological alterations in experimentally induced chronic selenosis by feeding selenium rich wheat straw (8.54 ppm) were studied in 18 non-descript buffalo calves. The clinical signs appeared after 35-45 days. The cardinal signs of induced selenosis were malformation of hoov.es and horns along with inflammation of coronary band, anaemia, alopecia, emaciation followed by death. Haematological indices revealed macrocytic - normochromic anaemia.